THE CORRELATION OF SIZE AND SEDIMENT ORGANIC MATTER WITH MAKROZOOBENTHOS ABUNDANCE IN MEDANG KAMPAI DUMAI CITY - Novhitasari Simbolon; Afrizal Tanjung; Elizal Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted in March 2019 at MedangKampai Waters of Dumai City. This study aims to determine the relationship between particle size and sediment organic matter with abundance of macrozoobenthos in MedangKampai waters. The method used is survey. Determination of stations using purposive sampling method. Sampling was carried out in the field and then taken to the Marine Chemistry Laboratory for analysis of sediment and organic material fractions. The identification of macrozoobenthos was carried out at the Marine Biology Laboratory. The results of the study of sediment fractions showed different types of sediments, namely sandy mud, gravel sand, and mud. Particle size and density of silt sediments (4.90 - 7.30 Ø). The content of organic ingredients is 3.37% - 19.40%. And the abundance of macrozoobenthos ranges from 1.11 ind / m2 - 3.56 ind / m2 with 16 numbers of species found from the dominating class of gastropods. The relationship of sediment particle size (Mz) to the abundance of macrozoobenthos has a value (r) = 0.0721 a very weak relationship (H0.1 is accepted). The relationship between the total organic matter content of sediments and the abundance of macrozoobenthos has a value (r) = 0.1044 which means it has a very weak relationship (H1.1 is accepted). Keywords: Particle Size, Organic Material, Macrozoobenthos,